A Bipolar Output Active-Switched-Inductor Converter for Bipolar DC Microgrid. (19th January 2022) - Guo, Yingjun; Sun, Hexu
Abstract : A bipolar DC microgrid shows good performance since it improves the efficiency and system's reliability. To transmit power to the load, several DC-DC converters are required by the conventional bipolar DC microgrid, which results into large weight, volume, and high cost. To integrate bipolar DC microgrid with the photovoltaic (PV) module, a novel bipolar output converter is proposed in this paper. This converter possesses very simple circuit configuration and can achieve a high step-up voltage gain by adopting active-switched-inductor (ASL) network; meanwhile, bipolar output voltage is between positive line (P), negative line (N), and common ground (O), which can offer three voltage classes (Vdc, +0.5 Vdc and -0.5 Vdc). To verify the precision of the analysis of the proposed converter, a prototype has been designed and experiments are performed in the lab.